PELATIHAN BUDIDAYA IKAN DAN SAYURAN DALAM EMBER (SISTEM AQUAPONIK) DI KAMPUNG MOSSO, DISTRIK MUARA TAMI, KOTA JAYAPURA - Tasak, Albida Rante; Kubelaborbir, Triana Mansye; Ingratubun, Jotje Aquarista; Mandibondibo, Paulus; Arief, Geraldy; Ayer, Popi Ida (Jurnal Abdi Insani, 2025)
Mosso is one of the villange in Muara Tami District, Jayapura City, Papua Province and it is aslo  located in in the border between Indonesia and Papua New Guinea.  The economy activities to support the local people’s livelihhod living in  Mosso village is a tradisional  farmers and the majority of them are farmers with   subsistence  agriculture.  The development in Mosso village is face the challenge due to the capacity of local people and this issue leads to the limitation of economic activities .  Budidamber is a combination technique of cultivating fish and vegetables in one container and this technique is also environmentally friendly that is promoted to apply in Mosso village. Catfish is one of commodities that has a high demand among Indonesia People. The reason why catfish and vegetables because the maintenance is easy and simple. This community service is aim to enhance the capacity building of local people in Mosso in terms of skills and knowledge about Budidamber so it can be benefit to their economic activities in household level. This community service is also aim to motivate local people in Mosso to do a simple cultivating fish with the limited land. The community service is taken place in Mosso Village, Muara Tami District Jayapura City on September 2023. The method of this activities is socialization and demonstration the practical of Budidamber. The material of this activities is delivered by some lecturer from Faculty of Agriculture, Forestry and Marine Ottow Geissler University related to the development of Budidamber such as design method, assembly technique, feeding technique and nutrition which is contain in Catfish and Water Spinach.  After delivering the material, further training is carried out. It is started with an introduction to tools and materials. Budidamber is an effective system and can be implemented without requiring a large budget or capital. It is hoped that this activity can also increase community knowledge in utilizing empty land in the yard and increase food security with the Aquaponics system